ANALISIS EFEKTIFITAS SARANA DAN PRASARANA DALAM MENDUKUNG PROSES BELAJAR SISWA BERKEBUTUHAN KHUSUS: STUDI KASUS DI SEKOLAH LUAR BIASA - Musyafa, Ahmad; Darmawan, Luqi; Subir, Muhammad Syuhada' (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the Analysis of the Effectiveness of Facilities and Infrastructure in Supporting the Learning Process of Students with Special Needs: Case Study in Special Schools. Type of qualitative research. Location at SLBN Punung. Data collection techniques with observation, interviews, documentation. Data analysis with triangulation. Based on the analysis of the effectiveness of facilities and infrastructure in Special Schools (SLB), it can be concluded that the availability and utilization of facilities and infrastructure that are in accordance with the needs of students with special needs play a very important role in supporting an optimal learning process. Adequate facilities, such as disability-friendly classrooms, special learning aids, and a safe and comfortable environment, have been proven to be able to increase student participation, concentration, and understanding in learning activities. However, there are still several obstacles in terms of maintenance and the limited number of aids that need attention to improve the effectiveness of educational services in SLB as a whole.